S-BPM ONE - Learning by Doing - Doing by Learning Third International Conference, S-BPM ONE 2011, Ingolstadt, Germany, September 29-30, 2011. Proceedings - Schmidt, Werner (Springer eBooks., 2011)
This book constitutes the thoroughly refereed post-proceedings of the Second International Conference on Subject-Oriented Business Process Management, S-BPM ONE 2010, held in Karlsruhe, Germany in October 2010. The 10 revised full papers presented together with one invited keynote paper and three panel statements were carefully reviewed and selected from initially 17 submissions. The papers present innovative cross-disciplinary ideas, concepts, methods, tools and results in foundational and applied research as well as studies on the realization of such innovations in the real world - all based on the promising new paradigm of subject-oriented business process management.